The European Union in the G20: what role for small states?. Issue 1 (2nd January 2016) - Nasra, Skander; Debaere, Peter
Abstract : The G20 has emerged as the premier forum for international economic policy coordination. For small EU states, the EU's participation in the G20 represents a particular challenge as they may be faced with decisions in which they had no say. This article looks at the possibilities for small state involvement in the G20 process and analyses the extent to which they can influence the EU's participation in the G20. The article suggests two sets of variables to explain the possibilities for influence of small states in the EU's external relations. Looking into four financial and economic policy dossiers, the article explores the conditions of success of small states' strategies. The article does not contradict that the big member states dominate the EU presence in the G20, but it does argue that small states may successfully use the EU as a foreign policy platform to pursue national objectives. Their influence varies strongly and is bound to a number of conditions.